Biological Microarrays Methods and Protocols - Khademhosseini, Ali.; Suh, Kahp-Yang.; Zourob, Mohammed; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Recent developments in microarray technology have changed the landscape of biology and biomedical research, and they have revolutionized RNA and DNA research. In Biological Microarrays: Methods and Protocols, expert researchers explore exciting new developments in the field, providing a comprehensive approach to biological microarrays that conveys not only the state-of-the-art fundamentals, but also includes applications of the most innovative methods. Chapters address both the application of biological microarrays, including DNA/RNA, apatmer, proteins, tissues, oligonucleotides, carbohydrates, biomaterials, cells, bacteria, and virus microarrays, and also explore the different techniques used for generating microarray platforms. Composed in the highly successful Methods in Molecular Biology™ series format, each chapter contains a brief introduction, step-by-step methods, a list of necessary materials, and a Notes section which shares tips on troubleshooting and avoiding known pitfalls. Wide-ranging and revolutionary, Biological Microarrays: Methods and Protocols serves as a primary source for academics, practitioners, and professionals in related fields, including biologists, biotechnologists, biochemists, analytical chemists, and biomedical, physical, and microsystems engineers, to name a few, appealing to all of those interested in the present and future state of biological microarray research.
RNA and DNA Microarrays -- Aptamer Arrays -- Oligonucleotide microarrays for identification of microbial pathogens and detection of their virulence-associated or drug-resistance determinants -- Protein MicroArrays printed from DNA MicroArrays -- Lithographically-defined two- and three-dimensional tissue microarrays -- Ratiometric lectin microarray analysis of the mammalian cell surface glycome -- Cell microarrays based on hydrogel microstructures for the application to cell-based biosensor -- Fabrication of Bacteria and Virus Microarrays Based on Polymeric Capillary Force Lithography -- 3D Polymer Scaffold Arrays -- PDMS microfluidic capillary systems for patterning proteins on surfaces and performing miniaturized immunoassays -- Merging Photolithography and Robotic Protein Printing to Create Cellular Microarrays -- Generation of Protein and Cell Microarrays on Functionalized Surfaces -- Microprinting of Liver Micro-organ for Drug Metabolism Study -- Microcontact printing -- Micromolding for the Fabrication of Biological Microarrays -- Progress Report on Microstructured Surfaces Based on Chemical Vapor Deposition -- Methods for Forming Human Microvascular Tubes in Vitro and Measuring Their Macromolecular Permeability -- Microarray Bioinformatics.
Keywords: Biotechnology; Human genetics; Biotechnology; Human Genetics